Composición química de la madera de tres especies de eucalipto - Coello Ruiz, Irak (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
To achieve this work, was necessary to pick a seven years old tree from three eucalypt species (Eucalyptus citriodora, E. robust and E. saligna) coming from an experimental plantation of Crisoba Industrial S. A. de C. V., planta Morelia. Two heights samplers of each tree was taken, which ones were separated in zones (sapwood and heartwood) to make chemical analysis determination chemical properties: pH, ash content, extraible substances solubility (in ascendant polarity solvents and hot water), lignin and holocelulloce quantification. Identification and quantification from sugars presents in wood was realized too. Once the chemical analysis finalized, calorific power determination was realized on woodmeal without extract and free extract woodmeal from sapwood and heartwood. The processed and statistically analyzed results indicate that: for pH exists a statistic difference between species, being E. robust more acid. Down part is more acid than high part, and heartwood is more acid than sapwood; the ashes content was bigger in E. citriodora regarding the other two species, without statistic difference between heights, and existing on sapwood a bigger presence of ashes content than heartwood; as for the extractives quantity, E. robust was the specie with higher percent and E. saligna the one with lowest percent, registering statistic difference between species, founding in the down part of the tree a higher quantity of them than in higher part and at the same time on heartwood; the specie with the bigger quantity of lignina was E. saligna differing of E. citriodora who present the lowest quantity, the bigger proportion was found in down part nor the higher and on sapwood nor heartwood; holocelullose percent equally results being bigger in E. citriodora and the specie with the lowest percent of holocelulloce was E. robust , down part presents more holocelulloce presence than higher part and there is not statistic difference in sapwood and heartwood. On the three species was identified Glucose, Xilose, Arabinose, Galactose and Mannose, being both, Glucose and Xilose, the sugars who present a higher proportion referring to Arabinose and Galactose in particular, therefore the Mannose percent resulting was very low; E. saligna was the specie, out of the three, who presented the higher percent of sugars. The calorimetric analysis carried out on sapwood and heartwood showed the best results in the woodmeal without extract, where the higher values happened on the eucalypts sapwood.

Para la realización de éste trabajo fue colectado un árbol de tres especies de eucalipto (Eucalyptus citriodora, E. robusta y E. saligna) de siete años de edad, procedentes de la plantación experimental de Crisoba Industrial S. A. de C. V., planta Morelia. Se tomaron muestras de cada árbol a dos alturas, las cuáles se separaron en zonas (albura y duramen) para realizar el análisis químico, determinando las propiedades químicas: pH, contenido de cenizas, solubilidad de sustancias extraíbles (en solventes de polaridad ascendente y agua caliente), cuantificación de lignina, y de holocelulosa. Se realizó también la identificación y cuantificación de azúcares presentes en la madera. Una vez terminado el análisis químico se llevó a cabo la determinación de poder calorífico en harina sin extraer y harina libre de extractos de albura y duramen. Procesados y analizados estadísticamente los resultados indicaron que: para pH existe diferencia estadística entre especies siendo más ácido E. robusta, la parte baja es más ácida que la alta y el duramen es más ácido que la albura; el contenido de cenizas fue mayor en E. citriodora respecto a las otras dos especies, sin diferencia estadística entre alturas, y existiendo en albura mayor cantidad de cenizas que en duramen; en cuanto a la cantidad de extraíbles E. robusta fue la especie con el mayor porcentaje y E. saligna con menor, teniendo entre las especies diferencia estadística, también se encontró en la parte baja del árbol más cantidad de los mismos que en la parte alta, y a su vez en el duramen; la especie con mayor cantidad de lignina fue E. saligna, y E. citriodora fue la que tuvo la menor cantidad, se encontró mayor proporción en la parte baja que en la alta y en la albura más que en el duramen; el porcentaje de holocelulosa igualmente resultó ser mayor en E. citriodora y la especie con menor cantidad de holocelulosa fue E. robusta , la parte baja presenta más holocelulosa que la parte alta y no hay diferencia estadística en albura y duramen. Se identificaron en las tres especies Glucosa, Xilosa, Arabinosa, Galactosa y Manosa, siendo Glucosa y Xilosa los azúcares que más proporción presentan referidos a Arabinosa y Galactosa en particular, puesto que la Manosa resultó muy baja en porcentaje; E. saligna fue el que más porcentaje de azúcares presentó de las tres especies. El análisis de calorimetría llevado a cabo en albura y duramen mostró los mejores resultados en la harina sin extraer y los valores más altos se registraron en la albura de los eucaliptos.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2006-0002; Madera; Eucalipto; PH; Cenizas; Lignina; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/158